Attachment aware schools and teachers. (2nd October 2021) - Zsolnai, Anikó; Szabó, Lilla
ABSTRACT: Primary attachment plays a fundamental role in children's social and emotional development and psychological well-being. Secure attachment correlates strongly with better social competence, self-regulation, well-being and school achievement. There is no full agreement among researchers investigating attachment as to what extent primary attachment determines the development of subsequent attachments. Numerous studies indicate that early attachment patterns may change and can be changed under the impact of the environment. In a safe school environment, a positive change can be promoted and supported by teachers.